Life Stress, Religiosity, and Personal Adjustment of Indonesian as International Students - Hutapea, Bonar (Makara Human Behavior Studies in Asia, 2014)
Understanding adaptation problem in international context is necessary as a source from which host universities formulate support services and counseling provision as well as for preparation before departure for international students. Although research on adjustment has burgeoned over the past several decades, relatively little is known about overseas student, particularly among Indonesian students as expatriates in some countries around the world. The present study is intended to examine the relationship of their life stress, religiosity, and adjustment. Data from 96 Indonesian international students were collected using demographic questions, personal adjustment scale, religiosity scale, and Index of Life Stress. Results revealed that the samples experienced moderate life stress, high religiosity, and high personal adjustment. Moreover, it was found that religiosity did not serve as moderator in the relationship between life stress and adjustment. Further, source of education financial support, as a part of general living issues, has unique contribution to their adjustment. Implication and limitations of this study are discussed in term of further research.